2020
DOI: 10.5137/1019-5149.jtn.31127-20.3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic and anti-oxidant effects of systemic uridine treatment in an experimental model of sciatic nerve injury

Abstract: AIM:To investigate the anti-apoptotic and anti-oxidant effects of systemic uridine treatment in a rat model of sciatic nerve injury.MATERIAL and METHODS: Thirty-two adult male rats were equally randomized to Sham, Control, U100, and U500 groups. Sham rats received a sham operation by exposing the right sciatic nerve without transection, while those in the Control, U100, and U500 groups underwent right sciatic nerve transection followed by immediate primary anostomosis. Sham and Control groups received saline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Animal studies also demonstrated a dose-dependent decrease by uridine of apoptotic markers Caspase-3, oxidative markers myeloperoxidase (MPO) and malondialdehyde (MDA) in sciatic nerve tissue of rats with sciatic nerve injury. Mechanistically, uridine serves as a precursor for the synthesis of cytidine-5′-diphosphocholine (CDP-choline), a rate-limiting endogenous intermediate in phospholipid synthesis, which is necessary for nerve growth ( Khezri et al, 2021 ).…”
Section: Uridine and Peripheral Neuropathymentioning
confidence: 99%
“…Animal studies also demonstrated a dose-dependent decrease by uridine of apoptotic markers Caspase-3, oxidative markers myeloperoxidase (MPO) and malondialdehyde (MDA) in sciatic nerve tissue of rats with sciatic nerve injury. Mechanistically, uridine serves as a precursor for the synthesis of cytidine-5′-diphosphocholine (CDP-choline), a rate-limiting endogenous intermediate in phospholipid synthesis, which is necessary for nerve growth ( Khezri et al, 2021 ).…”
Section: Uridine and Peripheral Neuropathymentioning
confidence: 99%
“…It has been demonstrated that 9H-purin-6-ol (also known as hypoxantine) tends to increase in hypoxic conditions [79]; since in our O 3 -treated samples hypoxantine decreased, we may assume that this effect could be due to the hyperoxygenation induced by O 3 . The uridine decrease may be related to its capability to stabilise energy metabolism as well as to its antioxidant capacity [80,81].…”
Section: The Modifications Of Amino Acid Carbohydrate Lipid and Nucle...mentioning
confidence: 99%